Biodiversità delle Aleocharinae della Cina: Lomechusini e Thamiaraeini (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2012)
Description of 21 new species of the tribes Lomechusini and Thamiaraeini belonging to the genera Orphnebius (O. uncinatus n. sp.), Tetrabothrus (T. chinensis n. sp.), Drusilla (D. damingensis n. sp., D. cenwanglaomontis n. sp., D. gilva n. sp., D. sinicola n. sp.), Zyras (Z. qingchengensis n. sp., Z. sichuanorum n. sp., Z. yongshengensis n. sp., Z. diaoluomontis n. sp., Z. fellowesi n. sp.), Pedinopleurus (P. jiuwanmontis n. sp.), Eutaenoglossa (E. schuelkei n. sp.), Platorischna (P. sinensis n. sp., P. sichuanensis n. sp.), Lasiokoryphina n. gen. (L. sinica n. sp.), Medeterusa (M. chinensis n. sp.), Mimacrotona (M. chinensis n. sp.), Mimoxypoda (M. sinica n. sp., M. sinorum n. sp.), Litoglossa (L. chinensis n. sp.). Each new species is illustrated and compared with similar species. Additional distributional data are reported for 14 species. The new genus Lasiokoryphina is similar to Platorischna. Drusilla hanoiensis Paśnik, 2000 is placed in synonymy with Zyras rufithorax Cameron, 1930. New combination is proposed for 1 species.SommarioDescrizione di 21 nuove specie delle tribù Lomechusini e Thamiaraeini appartenenti ai generi Orphnebius (O. uncinatus n. sp.), Tetrabothrus (T. chinensis n. sp.), Drusilla (D. damingensis n. sp., D. cenwanglaomontis n. sp., D. gilva n. sp., D. sinicola n. sp.), Zyras (Z. qingchengensis n. sp., Z. sichuanorum n. sp., Z. yongshengensis n. sp., Z. diaoluomontis n. sp., Z. fellowesi n. sp.), Pedinopleurus (P. jiuwanmontis n. sp.), Eutaenoglossa (E. schuelkei n. sp.), Platorischna (P. sinensis n. sp., P. sichuanensis n. sp.), Lasiokoryphina n. gen. (L. sinica n. sp.), Medeterusa (M. chinensis n. sp.), Mimacrotona (M. chinensis n. sp.), Mimoxypoda (M. sinica n. sp., M. sinorum n. sp.), Litoglossa (L. chinensis n. sp.). Ogni nuova specie è illustrata e comparata con specie simili. Sono riferiti dati aggiuntivi sulla distribuzione per 14 specie. Il nuovo genere Lasiokoryphina è affine a Platorischna. Drusilla hanoiensis Paśnik, 2000 è posta in sinonimia di Zyras rufithorax Cameron, 1930. E’ data una nuova combinazione.KeywordsColeoptera, Staphylinidae, Aleocharinae, taxonomy, China.Nomenclatural Actscenwanglaomontis Pace, 2012 (Drusilla), spec. nov.damingensis Pace, 2012 (Drusilla), spec. nov.gilva Pace, 2012 (Drusilla), spec. nov.philippina (Bernhauer, 1915) (Drusilla), comb. nov. hitherto Astilbus philippina Bernhauer, 1915sinicola Pace, 2012 (Drusilla), spec. nov.schuelkei Pace, 2012 (Eutaenoglossa), spec. nov.sinica Pace, 2012 (Lasiokoryphina), spec. nov.chinensis Pace, 2012 (Litoglossa), spec. nov.chinensis Pace, 2012 (Medeterusa), spec. nov.chinensis Pace, 2012 (Mimacrotona), spec. nov.sinica Pace, 2012 (Mimoxypoda), spec. nov.sinorum Pace, 2012 (Mimoxypoda), spec. nov.uncinatus Pace, 2012 (Orphnebius), spec. nov.jiuwanmontis Pace, 2012 (Pedinopleurus), spec. nov.sichuanensis Pace, 2012 (Platorischna), spec. nov.sinensis Pace, 2012 (Platorischna), spec. nov.chinensis Pace, 2012 (Tetrabothrus), spec. nov.Lasiokoryphina Pace, 2012 (Thamiaraeini), gen. nov.diaoluomontis Pace, 2012 (Zyras (Rhynchodonia)), spec. nov.fellowesi Pace, 2012 (Zyras (Rhynchodonia)), spec. nov.qingchengensis Pace, 2012 (Zyras (Zyras)), spec. nov.sichuanorum Pace, 2012 (Zyras (Zyras)), spec. nov.yongshengensis Pace, 2012 (Zyras (Zyras)), spec. nov.